Compression of X-ray free electron laser pulses to attosecond duration - Sadler, J; Nathvani, R; Oleśkiewicz, P; Ceurvorst, L; Ratan, N; Kasim, M; Trines, R; Bingham, R; Norreys, P (Nature Publishing Group, 2015)
State of the art X-ray Free Electron Laser facilities currently provide the brightest X-ray pulses available, typically with mJ energy and several hundred femtosecond duration. Here we present one- and two-dimensional Particle-in-Cell simulations, utilising the process of stimulated Raman amplification, showing that these pulses are compressed to a temporally coherent, sub-femtosecond pulse at 8% efficiency. Pulses of this type may pave the way for routine time resolution of electrons in nm size potentials. Furthermore, evidence is presented that significant Landau damping and wave-breaking may be beneficial in distorting the rear of the interaction and further reducing the final pulse duration.